The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1002/aoc.376
|View full text |Cite
|
Sign up to set email alerts
|

Review: Reactive selenium metabolites as targets of toxic metals/metalloids in mammals: a molecular toxicological perspective

Abstract: Human activities have been contaminating the environment with toxic heavy metal and metalloid compounds. Since the toxicity of one metal or metalloid can be dramatically modulated by the simultaneous ingestion of another, studies addressing the molecular basis of chemical interactions between toxic and essential elements are increasingly important. The intravenous injection of rabbits with selenite and arsenite or with selenite and mercuric mercury resulted in the in vivo formation of the seleno-bis (S-glutath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 92 publications
(66 reference statements)
1
29
0
Order By: Relevance
“…Similarly, the lower concentration of As (the metalloid) was observed in whole blood of lambs fed experimental diets with CA, irrespective of the presence of SeY and SeVI, as compared to control and ROFO diets. Antagonistic interactions are observed between Se-compounds and As-species in mammal tissues (Gailer, 2002).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Similarly, the lower concentration of As (the metalloid) was observed in whole blood of lambs fed experimental diets with CA, irrespective of the presence of SeY and SeVI, as compared to control and ROFO diets. Antagonistic interactions are observed between Se-compounds and As-species in mammal tissues (Gailer, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…At physiological pH, selenohydryl groups (RSeH) exist almost completely in an anionic form: [RSe-] − (unlike the sulpfhydryl group which exists almost in the protonated form: RSH). The anionic form of the selenohydryl group is a nucleophile that binds ions of metalloids and heavy metals (Gailer, 2002). So, it can be concluded that dietary SeY (group IV) more effectively stimulated the biosynthesis of metal binding Se-biomolecules in whole blood than SeVI (group V).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…with potential in vivo molecular targets are needed in order to unravel all biochemical mechanisms that are involved in their toxic effects at the organ level. To this end, the vast majority of studies that have been conducted so far have focused on the individual interaction of each metal with plasma proteins (e.g., human serum albumin) (Lau and Sarkar 1979), transmembrane proteins in erythrocytes (e.g., the hexose transport protein) (Vansteveninck et al 1965), intracellular sulfhydryl compounds (e.g., L-cysteine, L-glutathione (Rabenstein 1989) and proteins) andmore recently-reactive selenium metabolites (Gailer 2002). It has been known for a long time, however, that small concentrations of toxic metals can also produce appreciable changes of surface tension and surface charge in phospholipid bilayers (Passow et al 1961) and can increase the permeability of liposomes (Nakada et al 1978).…”
Section: Introductionmentioning
confidence: 99%